Early harvesting of rainfed plant cane to prevent heavy infestations of Eldana saccharina (Lepidoptera, Pyralidae) in Ferké Sugarcane plantations, Ivory Coast - (:unkn) unknown (My University, 2019)
The African stalk borer Eldana saccharina is an endemic pest of high economic importance in sub-Saharan Africa which often causes heavy infestations in rainfed plant cane subjected to a cycle of 15-17 months. The present study aimed to reduce overall damage due to this borer by early harvesting of sugarcane at three different periods. It involved two experiments carried out in Ferké 1 and Ferké 2 sugar estates over 17 months in rainfed plant cane, following a randomized complete block design (RCBD) with four different treatments. Treatments were composed of three harvesting periods (T1: November 15, T2: December 15, and T3: January 15), and a control (T0, no harvest), all in 4 replicates. The Ferké 1 experiment was planted with the variety N21 on 25/07/2017 and harvested on 23/06/2019. That of Ferké 2 was planted on 15/06/2017 with the variety M2592/93 and harvested on 05/12/2018. The study showed that variety N21 with high fiber content was more tolerant to stem borer than variety M2593/92 credited with a moderate fiber content. Stem borer infestations were significantly reduced across crop cycle following early harvesting on M2593/92, as opposed to N21. Without early harvesting, M2593/92 was much more infested than N21, with respectively 24 and 10% of internodes bored. Data showed that early harvesting in rainfed plant cane could be beneficial in the prevention of heavy infestations due to E saccharina.
Keywords: African Research